Trichoderma asperellum (T42) and Pseudomonas fluorescens (OKC)-Enhances Resistance of Pea against Erysiphe pisi through Enhanced ROS Generation and Lignifications - Patel, Jai S.; Kharwar, Ravindra N.; Singh, Harikesh B.; Upadhyay, Ram S.; Sarma, Birinchi K. (Frontiers in Microbiology, 2017)
Plant signalling mechanisms are not completely understood in plant-fungal biotrophic pathogen interactions. Further how such interactions are influenced by compatible rhizosphere microbes are also not well studied. Therefore, we explored the pea-Erysiphe pisi (obligate biotroph) system to understand the interaction and applied compatible rhizospheric bio-agents Trichoderma asperellum (T42) and Pseudomonas fluorescens (OKC) singly or in combination to assess their influence on the host while under the pathogen challenge. Transcript accumulation pattern of some vital genes in the lignin biosynthetic pathway in pea under E. pisi challenge indicated enhanced activation of the pathway. Interestingly, transcript accumulations were even higher in the bio-agent treated plants compared to untreated plants after pathogen inoculation particularly in co-inoculated treatments. Further, down regulation of the lignifications-associated ABC transporter gene in the pathogen challenged plants possibly is an indication of passive diffusion of monolignols across the membrane from symplast. Additionally, up regulation of NADPH oxidase gene revealed ROS generation in the challenged plants which was confirmed through spectrophotometric estimation of H2O2. Up regulation of laccase and peroxidase along with higher H2O2 generation points out their involvement in lignifications which was further confirmed through cross section analysis of pea stems that showed increased lignifications in pathogen challenged plants co-inoculated with the bioagents. Interestingly, pathogen responsive MAPK homologs MAPK3/MAPK6 and the enzyme serine threonine kinase (STK) that activates MAPKs were down regulated and the results possibly indicate non-participation of the MAPK cascade in this interaction. Therefore, it can be concluded that the microbial treatments enhanced pea resistance to E. pisi by generation of ROS and lignifications.